Fidelidade e esperança: as comuniddes entre o pluralismo religiosos e as perseguições em Apocalipse 2,1-7 - Oliveira, Juarez Dornelles de (2011)
The objective of the research was to analyze the text in the Letter to the Christian Community of Ephesus. (Ap 2,1-7), the general literary characteristics, the structure, the literary genre, the purpose, the context of the community in its Christian way of life, the challenges and responses during persecution in the Roman Empire and in the adversity of religious pluralism in the post-apostolic time (96-130 AD), thus building some ways to help the present Christian communities to face their own challenges. By means of a bibliographical approach, a study review was conducted, based on the axis text-context, with the adoption of content analysis on two levels: critical or contextual analysis and text analysis. The first chapter presents the historical context in which the text was produced: time and sociopolitical, economic and religious reality in Asia Minor and in the city of Ephesus in the 1st century AD, the persecution and religious plurality of the Christians in the Ephesians community, during the post-apostolic period. The chapter also brings the reflections of the historical moment of persecution and religious plurality in the practice and life of the Christians in the Ephesians community, in order to help elucidate the steps they took to respond to the challenges caused by the persecution in the Roman Empire and the religious plurality in Asia Minor. The second chapter is about the general literary characteristics, the origin and the formation of the apocalyptic movement, the time, the place, the addressees, the structure, the literary genre and the purpose of the text in Ap 2,1-7. The third chapter presents the analysis of the path taken by the Base Ecclesial Communities in Brazil and in the Diocese of Rondonopolis MT, the reflection and the construction of some responses, in light of Ap 2,1-7, of how communities may respond to the present challenges. Looking at the third generation of Christian communities has been an analytical exercise, inspiring alternatives for community life that need to be built in face of the challenges posed to Christians in our time. The text in Ap 2,1-7 may be taken as a parameter, for it reveals our Christian identity, an identity that should not be subject to change in adverse times and that should lead us to a more enthusiastic testimony and fidelity in following Jesus.